Identifying the interdependence between US monetary policy and the stock market - Hilde C. Bjørnland; Kai Leitemo (Bank of Finland, 2005)
We estimate the interdependence between US monetary policy and the S&P 500 using structural VAR methodology.A solution is proposed to the simultaneity problem of identifying monetary and stock price shocks by using a combination of short-run and long-run restrictions that maintains the qualitative properties of a monetary policy shock found in the established literature (CEE 1999).We find great interdependence between interest rate setting and stock prices.Stock prices immediately fall by 1.5 per cent due to a monetary policy shock that raises the federal funds rate by ten basis points.A stock price shock increasing stock prices by one per cent leads to an increase in the interest rate of five basis points.Stock price shocks are orthogonal to the information set in the VAR model and can be interpreted as non-fundamental shocks.We attribute a major part of the surge in stock prices at the end of the 1990s to these non-fundamental shocks.
URN:NBN:fi:bof-20140807357
Keywords: E61; E52; E43; 330; VAR; monetary policy; asset prices; identification